Two new Thereus species from Peru, with notes on ecological niche partitioning (Lepidoptera: Lycaenidae: Theclinae) - Faynel, Christophe; Fåhraeus, Christer (Zootaxa, 2023)
Male hairstreaks (Theclinae) are often territorial, known for occupying their observation posts at a specific time during the day and at a certain height in the vegetation. The time and height for their perch vary from species to species but remain surprisingly stable year after year in any particular location. From these strategic observation posts males can check the passage of virgin females and chase away competing males. Consequently, these posts act as resources for the males and are not only vigorously defended from conspecific males but also form males of other species. In Peru, males of two closely related species belonging to the genus Thereus Hübner were observed in situ, defending their territories. One of them, Thereus tierralinda Faynel & Fåhraeus, sp. nov., is described here based on five male specimens from Cosñipata valley, Cusco, southern Peru. Further, it is compared to Thereus columbicola (Strand) and other close species in the Thereus eryssus species group. Observations over several years of T. columbicola and this new species show that they have different spatial and temporal characteristics for their perches, presumably to avoid competition with one another. Additionally, as a result of the partial revision of the group, a second new species, Thereus vicens Faynel & Fåhraeus, sp. nov., is also described based on one male and two females from Tingo María, Huánuco, central Peru. We also note that French Guiana is a new country record for Thereus eryssus (Herbst).